Pengaruh Pengungkapan Emisi Karbon, Biaya Lingkungan, Conditional Conservatism, Profitabilitas, dan Firm Size terhadap Audit Fees - Rehatta, Verina Rebeca; Hasnawati, Hasnawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine and analyze the relationship between Carbon Emission Disclosure, Environmental Costs, Conditional Conservatism, Profitability, and Firm Size, and whether these variables influence Audit Fees. The population of this research consists of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. This study uses secondary data obtained from company annual reports. The sampling technique employed is purposive sampling, with an unbalanced panel data approach applied to 90 companies, resulting in 213 observations. The data analysis method used to test the hypotheses is Panel Data Regression, conducted using EViews 13 software. The findings reveal that Carbon Emission Disclosure and Environmental Costs have no significant effect on Audit Fees. Meanwhile, Conditional Conservatism, Profitability, and Firm Size have a positive effect on Audit Fees.